2018
DOI: 10.1371/journal.pone.0203110
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of major cancer statistics according to sex and severity levels in Korea

Abstract: Existing epidemiologic reports or studies of cancer statistics in Korea lack sufficient data on cancer severity distributions and observed survival rates. This study analyzed trends in major cancer statistics according to sex and severity levels in Korea from 2006 to 2013. We included eight cancers (hepatocellular carcinoma, and thyroid, colorectal, gastric, lung, prostate, breast, and cervical cancer), using Korea Central Cancer Registry data. Severity level was classified by Surveillance, Epidemiology, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Gender survival analysis of our cohort is in agreement with previous reports on gender survival difference in lung cancer, which revealed consistently improved survival for female patients [26][27][28][29][30]. In this study, the median overall survival for female patients with ESRD is 12.25 months (95% CI: 5.78-17.45) comparable to the 14.13 months (95% CI: 11.07-16.43) for female patients without ESRD, p = 0.996.…”
Section: Discussionsupporting
confidence: 92%
“…Gender survival analysis of our cohort is in agreement with previous reports on gender survival difference in lung cancer, which revealed consistently improved survival for female patients [26][27][28][29][30]. In this study, the median overall survival for female patients with ESRD is 12.25 months (95% CI: 5.78-17.45) comparable to the 14.13 months (95% CI: 11.07-16.43) for female patients without ESRD, p = 0.996.…”
Section: Discussionsupporting
confidence: 92%
“…According to Wisnivesky et al ., women have better lung cancer‐specific, overall, and relative survival than men in all treatment groups . The gender‐related differences in cancer affecting both sexes are more prominent in lung cancer at localized, regional, and unknown stages . Sagerup et al .…”
Section: Discussionmentioning
confidence: 99%
“…24 The genderrelated differences in cancer affecting both sexes are more prominent in lung cancer at localized, regional, and unknown stages. 26 Sagerup et al reported that regardless of stage, age, the period of diagnosis, and selected histological subgroups, men had an increased risk of death at fiveyears. 27 According to recent cancer statistics in the United States, the five-year relative survival by gender for all races was 21.5% for women and 15.4% for men.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant improvements in clinical outcomes related to the implementation of screenings, advances in surgical techniques and/or usage of (neo-)adjuvant chemotherapy and/or concurrent chemoradiotherapy, a considerable proportion of patients still experience recurrences and die of GC [2][3][4].…”
Section: Introductionmentioning
confidence: 99%